Aircraft leasing and financing : tools for success in international aircraft acquisition and management - Guzhva, Vitaly S.; Raghavan, Sunder; D'Agostino, Damon J. (Elsevier, 2019)
Aircraft Financing and Leasing: Tools for Success in Aircraft Acquisition and Management provides researchers, industry professionals and students with a thorough overview of the skills necessary for navigating this dynamic field. The book details the industry's foundational concepts, including aviation law and regulation, airline credit analysis, maintenance reserves, insurance, transaction cost modeling, risk management tools, such as fuel hedging, and the art of lease negotiations. Different types of aircraft are explored, highlighting their purposes, as well as when and why airline operators choose specific models over others. In addition, the book also covers important factors, such as maintenance reserve development, modeling financial returns for leased aircraft, and appraising aircraft values. Most chapters feature detailed case studies, applying concepts to actual industry circumstances. Users will find this an ideal resource for practitioners or as an outstanding reference for senior undergraduate and graduate students.